1997
DOI: 10.1042/bj3210075
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cell surface GLUT4 in skeletal muscle of transgenic mice

Abstract: Marked overexpression of the glucose transporter GLUT4 in skeletal muscle membrane fractions of GLUT4 transgenic (TG) mice is accompanied by disproportionately small increases in basal and insulin-stimulated glucose transport activity. Thus we have assessed cell surface GLUT4 by photolabelling with the membrane-impermeant reagent 2-N-[4-(1-azi-2,2,2-trifluoroethyl)benzoyl]-1, 3-bis(D-mannos-4-yloxy)-2-propylamine (ATB-BMPA) and measured the corresponding glucose transport activity using 2-deoxyglucose in isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 30 publications
3
34
0
Order By: Relevance
“…First, transgenic complementation of GLUT4 in EDL muscle from male and female GLUT4-null mice led to a significant increase in muscle glycogen levels. This finding is in agreement with several reports whereby increased muscle glycogen levels have been noted in GLUT4 transgenic mice (29,32,33,42) and suggests that enhanced glucose flux, presumably because of increased expression of GLUT4, leads to greater glycogen storage in skeletal muscle. Our finding that glycogen content in soleus muscle of male GLUT4-null mice was 45% lower than control levels supports this concept.…”
Section: Figsupporting
confidence: 83%
See 3 more Smart Citations
“…First, transgenic complementation of GLUT4 in EDL muscle from male and female GLUT4-null mice led to a significant increase in muscle glycogen levels. This finding is in agreement with several reports whereby increased muscle glycogen levels have been noted in GLUT4 transgenic mice (29,32,33,42) and suggests that enhanced glucose flux, presumably because of increased expression of GLUT4, leads to greater glycogen storage in skeletal muscle. Our finding that glycogen content in soleus muscle of male GLUT4-null mice was 45% lower than control levels supports this concept.…”
Section: Figsupporting
confidence: 83%
“…Furthermore, transgenic complementation of GLUT4 was sufficient to fully restore hypoxia-induced glucose transport in EDL muscle from MLC-GLUT4-null. In vitro exposure of isolated skeletal muscle to hypoxia, followed by re-oxygenation, is known to increase glucose transport (8,14,15,33,40,41) and GLUT4 recruitment to the cell surface (8,14). Because hypoxia appears to be a relevant model for exercise-stimulated glucose transport (8), our results suggest that GLUT4 is the only downstream effector of the muscle contraction/hypoxia pathway to glucose transport.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Previous studies have shown that insulin and exercise-contraction recruit different GLUT4 storage compartments in skeletal muscle through distinct signaling pathways (1, 11, 20, 29-31, 39, 50). Since hypoxia in vitro is a commonly used model for exercise-stimulated glucose transport (6,7,21,52), the isolated soleus muscles were also made hypoxic and assayed for glucose transport activity. Even though hypoxia was a weaker activator of glucose uptake than insulin, identical responses were obtained in both wild-type and VAMP3 null mice.…”
Section: Vol 21 2001 Targeted Disruption Of the Vamp3 Gene 1575mentioning
confidence: 99%